2022
DOI: 10.1017/dmp.2022.71
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Impacts of the COVID-19 Pandemic and the Recent Earthquakes: A Scoping Review of the Lessons Learned

Abstract: Objective: The aim of this study was to review the articles dealing with the mutual impacts of the coronavirus disease 2019 (COVID-19) pandemic and the recent earthquakes to elicit the various scopes of the lessons learned including the challenges, the successful measures, and the recommendations. Methods: To detect the relevant studies published between February 1, 2020, and June 9, 2021, PubMed, Web of Science, Scopus, and Google Scholar were searched. Having considered specific inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Despite some limitations, our findings expand the current knowledge on the impact of natural disasters on psychiatric patients, and highlight the vulnerability of psychiatric patients, particularly those with DAD disorders. However, among “dual psychological pressures” [ 22 ], earthquake appears to have more profound effects. Complete uncontrollability of earthquake may contribute to such fear-provoking effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite some limitations, our findings expand the current knowledge on the impact of natural disasters on psychiatric patients, and highlight the vulnerability of psychiatric patients, particularly those with DAD disorders. However, among “dual psychological pressures” [ 22 ], earthquake appears to have more profound effects. Complete uncontrollability of earthquake may contribute to such fear-provoking effects.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the fourth week of the epidemic in Croatia, when the experts thought that nothing worse could happen, on 22 March 2020, the citizens of Zagreb were awakened by an earthquake of 5.5 magnitude on the Richter scale, followed the 57 aftershocks in the next 24 h, and the extensive property damage [ 20 ], with 27 people being severely injured, of which one died [ 21 ]. Mutual impacts of the earthquakes and the pandemic represent a dual psychological challenge [ 22 ]. Several studies in Croatia addressed the impact of both disasters, by comparing their effects between exposed and non-exposed groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-incidence of COVID-19 with other hazards, such as a dam failure, exposed existing vulnerabilities, as disasters could be seen as processes resulting from "economic, political, and social constructions" [5]. A scoping review also identified the co-incidence of physical hazards with the occurrence of COVID-19, with negative impacts on resilience and lifestyle, but noting the key roles of women in responding to disaster [40]. This speaks to the continuing importance of work on resilience that seeks to quantify benefit of proactively addressing risks, to reduce the consequences of failure and improve times to recovery [41].…”
Section: The Impact Of the Covid-19 Pandemicmentioning
confidence: 99%